A randomized Phase 2 study of pemetrexed in combination with cisplatin or carboplatin as adjuvant chemotherapy in patients with completely resected stage IB or II Non-Small-Cell Lung Cancer. Issue 3 (December 2015) - Schmid-Bindert, Gerald; Engel-Riedel, Walburga; Reck, Martin; Schuette, Wolfgang; Stöhlmacher, Jan; Fischer, Jürgen R.; Mazières, Julien; Chouaid, Christos; Wolf, Martin; Vinolas, Nuria; Soldatenkova, Victoria; Ripoche, Veronique; et al.
Highlights: Feasibility of adjuvant cisplatin or carboplatin + pemetrexed in Stage IB/II NSCLC. Feasibility definition based on safety, tolerability, and dose-intensity parameters. Neither treatment met the pre-defined feasibility level >60% of patients. Feasibility >81% (both treatments) in a post-hoc analysis considering only safety. Both treatments showed good safety-related feasibility and tolerability. Abstract: Objectives: We investigated the feasibility of cisplatin or carboplatin combined with pemetrexed as adjuvant treatment in patients with completely resected Stage IB/II Non-Small-Cell Lung Cancer (NSCLC). Materials and methods: Patients in this multicenter, open-label, parallel-group, non-comparative Phase 2 study were randomized (1:1) to pemetrexed (500 mg/m 2 ) with either cisplatin (75 mg/m 2 ) or carboplatin (AUC5) for 4 cycles of 21 days. The primary endpoint was treatment feasibility (defined as 4 cycles completed with no cycle delay >42 days and ≤2 dose reductions, with a median relative dose intensity (RDI) ≥95% [overall]; and no Grade ≥3 toxicities at the follow-up visit 30 days after last drug administration). Secondary objectives included overall survival (OS) and safety. Results: We randomized 122 patients and treated 118. 71.9% (46/64) of patients in pemetrexed + cisplatin and 88.9% (48/54) in pemetrexed + carboplatin completed 4 cycles (median RDI >97% for all compounds). Neither treatment met the pre-defined feasibility level >60% of patients: 59.4% (95% confidence interval [CI]: 46.4;71.5) pemetrexed + cisplatin; 50.0% (95%CI: 36.1;63.9) in pemetrexed + carboplatin. In a post-hoc analysis considering only safety, both regimens were feasible with 81.3% (95%CI: 69.5;89.9) in pemetrexed + cisplatin and 90.7% (95%CI: 79.7;96.9) in pemetrexed + carboplatin. OS rates for both groups were 82–83% after 3 years and 80–83% after 5 years. Treatment-related Grade ≥3 adverse events (mostly hematological) were experienced by approximately 30% of patients in each group. Conclusion: Although the study did not meet the primary objective, both treatment groups demonstrated good safety-related feasibility and tolerability as adjuvant treatment in patients with completely resected Stage IB/II NSCLC.